PERLINDUNGAN PSIKOSOSIAL TERHADAP ANAK KORBAN TINDAK PIDANA PERKOSAAN DI PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Adult interest in sex that makes children an object is categorized as an act that is prohibited and threatened with criminal penalties based on Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. Rape experienced by children causes physical, psychological and social injury that can affect the quality of their lives in the future. The Government, Regional Government and State Institutions must provide special protection in the form of psychosocial assistance provided at each level of examination ranging from investigation, prosecution to examination at a court hearing. Psychosocial assistance is a combination of psychological and social treatments aimed at healing trauma to the victim so that it can grow and develop optimally.This type of research is sociological legal research, which means the writer directly conducts research at the location under study, namely Pekanbaru City Police, Integrated Women's and Child Empowerment Service Center (P2TP2A), Pekanbaru City Social Service, Riau Child Protection Agency. The population and sample in this study are all parties related to the problem under study. Source of data used are primary data and secondary data, while the data collection techniques in this study use interviews and literature studies.The results of the study that can be concluded are, firstly the implementation of psychosocial assistance to child victims of rape in Pekanbaru is only done during the police inspection process to complete the case report and sometimes it is not given and carried out at all, so the rights of the victim's child are not fulfilled in accordance with the Child Protection Law Act. Second, obstacles in the implementation of psychosocial assistance to child victims of rape in Pekanbaru are the unavailability of special service rooms, lack of communication between Law Enforcement Officers and Child Care Institutions, lack of Social Workers, and families / victims not reporting. The efforts made to overcome these obstacles are in collaboration with the Child Social Rehabilitation Center in Rumbai to use special service room facilities, request the addition of Social Workers and socializing to children and the community.Keywords: Psychosocial Assistance - Special Protection - Children Victims of Rape